The Feminist Interpretation in Literature. Delmira Agustini´s Example (Castilla. Estudios de Literatura, 2011)
Since a long time the feminist theories have been applied to the literary interpretation of the work produced by women writers, with the final aim of explaining the conflict that exists between the dominant male speech and the submerged world of the women that dare to write. From Simone de Beauvoir to Judith Butler, there have been many the female voices that have discussed about the anxiety of influence and authority by which women artists are affected. The example of Delmira Agustini is a paradigm, since she was the first Spanish-American poet who dared do show freely her female soul, a fact that was not understood in her hometown, Montevideo, which, at that time, was characterized by false modernity that laid under a deep conservatism. However, Delmira Agustini managed to develop a group of female masks to overcome these difficult times and create her own artistic world at last.